(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2023)
The effectiveness of any digital marketing strategy is strongly dependent on the user experience of the website being promoted. A website that is difficult to browse, confusing or slow to load the content can result in a poor user experience and, as a result there is a loss in leads or consumers. A website that is easy to use, well organized and optimised for mobile devices, on the other hand can help improve user engagement, raise conversion rates and ultimately boost the success of digital marketing initiatives. This paper shows the significance of website usability in digital marketing and explores the impact of website usability on user experience and how it can affect the key performance indicators such as bounce rates, session duration and conversion rates. By emphasising the importance of website usability in digital marketing, this paper intends to give actionable insights for business looking to improve the user’s website’s user experience and maximise the digital marketing campaigns. Understanding the impact of website usability on the performance of digital marketing efforts allows organisations to make informed decisions regarding website design and functionality to create good user experience that increases engagement and conversion.